Women and Whistleblowing: Exploring Gender Effects in Policy Design - Tilton, Clare (Columbia Journal of Gender and Law, 2018)
Laws that incentivize employees to blow the whistle when they perceive a financial risk and protect them from retaliation have sharply increased in popularity and have even become commonplace at the state level for fraud related to government money. Dodd-Frank codified a similar kind of protection for whistleblowers who report private-sector fraud. This Note suggests that states, especially New York, have an opportunity to propose new financial fraud whistleblower legislation in response to the Trump administration’s efforts to reduce the federal government’s active regulatory role in the financial sector. However, the prevalence and potential of such legislation should inspire a closer look at how legal mechanisms target and encourage participation across the employee population. Any program that seeks to encourage participation within an existing context, such as the financial services workplace, risks entrenching bias and inequality if it fails to consider the differential effects of its design across different demographics. This Note therefore addresses whistleblower laws’ implications for women employees’ participation in whistleblowing when they observe financial services sector-based misconduct. It reviews existing research regarding women’s participation in whistleblowing and considers how that evidence should shape choices of policymakers who seek to encourage employee reporting while still fostering workplace environments and regulatory structures that value and bene t from women’s voices.